2018
DOI: 10.1152/jn.00251.2017
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine enhances song responsiveness and encoding in the auditory forebrain of male zebra finches

Abstract: Norepinephrine (NE) can dynamically modulate excitability and functional connectivity of neural circuits in response to changes in external and internal states. Regulation by NE has been demonstrated extensively in mammalian sensory cortices, but whether NE-dependent modulation in sensory cortex alters response properties in downstream sensorimotor regions is less clear. Here we examine this question in male zebra finches, a songbird species with complex vocalizations and a well-defined neural network for audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 64 publications
1
17
2
Order By: Relevance
“…However, these changes in single-unit ACC responses were not related reliably to properties of the concurrently measured LC response that we could measure and thus may involve mechanisms other than the LC-NE system. These findings do not appear to be consistent with previous work showing improvements in signal-to-noise ratios in cortex in response to LC-NE activation or during states of higher versus lower global arousal (Kolta et al, 1978;Mclean and Waterhouse, 1994;Lee et al, 2018;Lombardo et al, 2018). This difference could reflect differences in the specific neurons that we targeted in ACC, the different task conditions we tested relative to previous studies, or both, and also merits further study.…”
Section: Discussioncontrasting
confidence: 85%
“…However, these changes in single-unit ACC responses were not related reliably to properties of the concurrently measured LC response that we could measure and thus may involve mechanisms other than the LC-NE system. These findings do not appear to be consistent with previous work showing improvements in signal-to-noise ratios in cortex in response to LC-NE activation or during states of higher versus lower global arousal (Kolta et al, 1978;Mclean and Waterhouse, 1994;Lee et al, 2018;Lombardo et al, 2018). This difference could reflect differences in the specific neurons that we targeted in ACC, the different task conditions we tested relative to previous studies, or both, and also merits further study.…”
Section: Discussioncontrasting
confidence: 85%
“…At the level of auditory circuitry, neuromodulators regulate the balance of excitatory and inhibitory pathways through presynaptic and postsynaptic mechanisms [ 53 , 54 , 55 , 56 , 57 ]. As a result, neuromodulators alter the ways that auditory neurons respond to acoustic stimuli ([ 58 , 59 , 60 ]; reviewed in [ 52 ]) and gate information from different sources through key circuit elements like projection neurons [ 56 , 61 ]. Neuromodulatory neurons may receive afferent information from a wide range of integrative brain systems, and therefore, have the potential to provide ‘value-added’ feedback to the auditory system.…”
Section: Social Isolation Can Occur With Hearing Lossmentioning
confidence: 99%
“…This study used female mice. Because it has been suggested that the auditory cortical responses during auditory stimulation including noise have sex-differences [33,34], the possible differences in male are warrant to be considered.…”
Section: Discussionmentioning
confidence: 99%